Hambatan Non-Tarif dan Dinamika Daya Saing Ekspor Kopi: Studi Komparatif Indonesia dan Vietnam - Nazla Atikah Hikmatias Nasution; Sahara; Novindra (Jurnal Penelitian Pendidikan IPA, 2026)
Indonesia is one of the world’s major coffee producers, however its export competitiveness remains relatively weaker and less stable than that of key competitors such as Vietnam. Previous studies on Indonesian coffee exports have largely focused on production and price dynamics, while the role of non-tariff barriers in shaping export competitiveness has received limited attention. This study therefore analyze the impact of non-tariff barriers on the competitiveness of Indonesian and Vietnamese coffee exports in major destination markets. The analysis employs the inventory approach, Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), Export Product Dynamics (EPD), and the Gravity Model using panel data of key importing countries during 2005-2024 period. The results indicate that Sanitary and Phytosanitary (SPS) measures are the most dominant non-tariff barriers, as reflected by the Frequency Ratio (FR) and Coverage Ratio (CR) indicators, with 17 incident codes regulating a significant share of coffee trade. The results show that Indonesian coffee maintains a comparative advantage, as reflected by RCA values above one and positive RSCA values; however, this advantage is lower and less stable than that of Vietnam. EPD analysis further confirms that Indonesia’s coffee exports are predominantly positioned in the lost opportunity, retreat, and falling star quadrants. Moreover, the estimation results indicate that both SPS and TBT significantly reduce the export competitiveness of Indonesian and Vietnamese coffee. These findings suggest that improving compliance with international standards, strengthening certification systems, and enhancing traceability and quality control are essential policy priorities for improving the global competitiveness of Indonesian coffee exports.